0196 Evaluating the use of a simulated ward round to improve medical students' confidence in paediatric skills. (2nd November 2015) - Carus, Catherine; Cooper, Matthew; Fishwick, Rebecca
Abstract : Background: Literature has shown that previous simulated ward rounds identified shortcomings predominantly in students' non-technical skills like prioritisation and communication. Also, no research was found regarding their use in paediatrics. For this reason, a simulated ward round was developed for the paediatric teaching programme in order to improve core skills in the context of a paediatric ward. Methodology: A 12 station ward round was created (8 patient and 4 non-patient stations). Students were split into four groups and given information about three stations. They then had 20 min to complete the three scenarios in any order. Students rotated until they had completed all 12 stations. Finally, students were asked to hand over the last 3 stations; this included a discussion with a teaching fellow about prioritisation and contributions from simulated patients about aspects like communication and explanation skills. A pre-simulation questionnaire assessed students' confidence in skills using a five-point scale, as well as a free-text section on what they hoped to achieve. This was followed up with a similar questionnaire post-event to assess how they subsequently rated their confidence. Results: 44 students have participated to date, with more sessions scheduled. Paired samples t-tests showed a statistically significant (p < 0.05) increase in students confidence in seven of the eight skills evaluated; handover skills (+0.91), and prioritisation (+0.89) showed the biggest mean increases. Every student recommended this activity. Analysing the free text, the commonest skills students felt had been improved were communication skills, prescribing skills and knowledge of paediatric problems. Conclusions: This simulation improved students' confidence in common skills required of a junior doctor in paediatrics. Students found the event useful and would recommend it. It is hoped this event can be developed further by incorporating students from other professions. References: Nikendei C, et al . Ward rounds: how prepared are future doctors? Med Teach 2008;30:88–91 McGregor CA, et al . Preparing medical students for clinical decision making: A pilot study exploring how students make decisions and the perceived impact of a clinical decision making teaching intervention. Med Teach 2012;34:e508–17 Ker JS, et al . Can a ward simulation exercise achieve the realism that reflects the complexity of everyday practice junior doctors encounter? Med Teach 2006;28:330–4 Smith SD, et al . A study of innovative patient safety education. Clin Teach 2012;9:37–40